Elite sprint technique kinematics - Mirzoev, O. M. (Theory and Practice of Physical Culture, 2018)
The study analyzes the technique kinematics of elite sprinters in the 2018 (XVII) IAAF World Indoor Championship in Birmingham, the UK. Subject to the analysis were the sprint technique elements including stride length and frequency rated in the 60m men`s final. The analysis of the individual sprint techniques demonstrated by 8 strongest competitors in two rounds of the event found the leading kinematic rates critical for the speed on distance. The study reports and analyzes the specific sprint speed, stride length and frequency data versus the competitive accomplishments of the best sprinters in the winter competitive season. The study data and analyses demonstrate the roles of the winter and summer World Championships for the world sprint elite.